Word search sequences: exploring the embodiment in L2 interaction - Abdullah, Nur Nabilah (2017)
Studies on face-to-face interactions have demonstrated how spoken language involves not only verbal but also mutual collaboration with the embodiment. The embodiment, such as gestures, can convey semantic content and can be a crucial point in a conversation (Hazel et al., 2014). In this study, I will investigate the embodiment that includes gaze, head movement, gestures and body posture that are displayed in word search phenomenon in L2 interaction. Word search is regarded as a type of repair in which the progressivity of the speaker’s turn is momentarily ceased because the speaker encounters trouble in formulating the talk (Schegloff et al., 1977). The setting of the study is non-educational where casual conversation among international university students having dinner at a cafe is recorded. The study is also a multi-activity setting in which multi-party participants are engaged in talking, eating and drinking. The participants, whom are L2 users, are from different countries and most of them have different first language background. English is used as a form of communication as it is the most common language that these international students resort to speaking with someone who has different language background. Using conversation analysis (CA), this study aims to explore how participants with different language expertise exploit these embodied resources in word search sequences. In this presentation, the finding warrants the following question of how L2 users organize participation through talk and embodiment in L2 interaction. A detailed description of the embodied resources such as gaze shift, head movement, gesture and body posture of both speaker and recipient will be discussed. Thus, these findings can enhance our understanding of how participation in word search phenomenon is negotiated and coordinated through talk and embodiment in a multi-party and multi-activity L2 interaction.